ANALISIS PERMINTAAN TENAGA KERJA PADA INDUSTRI KECIL DAN MENENGAH DI KABUPATEN GRESIK - Bela Oka Ariska (Jurnal Ilmu Ekonomi JIE, 2018)
Small and medium size enterprise in Gresik Residency experience such an incline trend in terms of labour demand which leads to the reduction of unemployment by creating job opportunities. This research aims at explaining several variables of: the influence of industry amount, investment value, production value and wage towards labour demand in Gresik Residency. The data used in this research is panel data from2014 to2016. Analysis method of this research is linier regression.The result of this research indicates that industry amount (X1) has a significantly positive influence value of 0.704962. The value of investment (X2) has a significantly negative influence value of -0.359888. The production value (X3) has a significantly positive influence value of 0.388117. Wage (X4) has an insificantly negative influence value of -0.149321.Keywords: Industryt, investment, production, wage